Longevity of posterior resin composite restorations in adults – A systematic review. Issue 8 (August 2015) - Ástvaldsdóttir, Álfheiður; Dagerhamn, Jessica; van Dijken, Jan W.V.; Naimi-Akbar, Aron; Sandborgh-Englund, Gunilla; Tranæus, Sofia; Nilsson, Mikael
Abstract Objective To conduct a systematic review of the literature on the longevity of posterior resin composite restorations in adults. Material and methods A systematic literature search was conducted according to pre-determined criteria for inclusion and exclusion. The studies selected were prospective clinical trials with a minimum follow-up time of 4 years, 40 restorations per experimental group and an annual attrition rate of less than 5%. Initially, abstracts and full-text articles were assessed independently and the assessment was subsequently agreed on by five reviewers. The methodological quality of the studies was assessed according to the Swedish Council on Health Technology Assessment (SBU) standard checklist for determining the extent to which studies meet basic quality criteria. Results In all, the literature search identified 4275 abstracts and 93 articles were read in full-text. There were eighteen studies which met the criteria for inclusion, eight of which were included in the analysis. There were 80 failures of restorations with a total follow-up time at risk for failure of 62, 030 months. The overall incidence rate for all causes of failure was 1.55 lost restorations per 100 restoration years. The most common biological reason for failure (a total of 31 restorations) was secondary caries, with or without fracture of the restoration. The quality of the evidence was low. Conclusions In an efficacy setting, the overall survival proportion of posterior resin composite restorations is high. The major reasons for failure are secondary caries and restoration fracture which supports the importance of adequate follow-up time. Clinical significance The overall survival proportion of posterior composite restorations was high, but the results cannot be extrapolated to an effectiveness setting. The importance of adequate follow-up time is supported by the finding that secondary caries often occurred after 3 years or later.